UPAYA PENINGKATAN KEMAMPUAN MENYUSUN PENELITIAN TINDAKAN KELAS MELALUI LOKAKARYA INTENSIF TERSRUKTUR BAGI GURU SDN 02 GURUN PANJANG - Elfina Elfina (JURNAL MANAJEMEN PENDIDIKAN, 2018)
ABSTRACTBased on the results of observations that the researchers have done to the Teachers at SDN 02 Long Desert, it was found that the Teacher's Ability to Arrange Research in classroom action was still low. The purpose of this study was to improve the ability of teachers to develop classroom action research through structured intensive workshops at SDN 02 Long Desert. This research is a school action research. The research procedures in this study include planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 7 teachers from SDN 02 Long Desert. The research data was collected using observation sheets. Data were analyzed using percentages. The results of the study show that through a Structured Intensive Workshop can increase the Teacher's Ability to Develop Classroom Action Research. This is evidenced by the increase in the ability of teachers to compile classroom action research in cycle I to cycle II. The average ability of teacher skills in the Teacher's Ability in Compiling Research in class action in the first cycle is 45.5 with the Less category and in the second cycle 84 is in the good category.